2017
DOI: 10.1021/jacs.6b12990
|View full text |Cite
|
Sign up to set email alerts
|

Substrate and Lewis Acid Coordination Promote O–O Bond Cleavage of an Unreactive L2CuII2(O22–) Species to Form L2CuIII2(O)2 Cores with Enhanced Oxidative Reactivity

Abstract: Copper-dependent metalloenzymes are widespread throughout metabolic pathways, coupling the reduction of O2 with the oxidation of organic substrates. Small-molecule synthetic analogs are useful platforms to generate L/Cu/O2 species that reproduce the structural, spectroscopic, and reactive properties of some copper-/O2-dependent enzymes. Landmark studies have shown that the conversion between dicopper(II)-peroxo species (L2CuII2(O22−) either side-on peroxo, SP, or end-on trans-peroxo, TP) and dicopper(III)-bis(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 49 publications
1
45
1
Order By: Relevance
“…Even though this is an unusual oxidation state of Cu, it has been identified earlier for similar Cu 2 O 2 motifs in enzymatic catalysts. 23,55,56 To investigate the effect of the incorporation of vdW interaction, the oxidation of Cu with oxygen in the gas phase is investigated using the BEEF and PBE-cx functionals. The spatial confinement in the zeolite cages is expected to give substantial vdW interactions with the Cu-complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Even though this is an unusual oxidation state of Cu, it has been identified earlier for similar Cu 2 O 2 motifs in enzymatic catalysts. 23,55,56 To investigate the effect of the incorporation of vdW interaction, the oxidation of Cu with oxygen in the gas phase is investigated using the BEEF and PBE-cx functionals. The spatial confinement in the zeolite cages is expected to give substantial vdW interactions with the Cu-complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Lewis acid adducts of peroxo complex [(TMC)­Fe III (O 2 )] + (left) and reversible O–O cleavage interconverting S P and O cores in Cu 2 O 2 intermediates mediated by the Lewis acid Sc 3+ (right) …”
Section: Introductionmentioning
confidence: 99%
“…Binuclear copper sites play an important role in enzymatic reactions as copper containing proteins are known to facilitate a range of zero-, two-or four-electron processes involving oxygen. [1][2][3][4] The nature of the active binuclear centers has been investigated extensively and characterized as being either coupled or non-coupled, depending on the distance between the metal sites. 2 Using model complexes, it has demonstrated that the Cu-Cu distance can be used as a design parameter to stabilize oxygen in different structural and electronic configurations.…”
Section: Introductionmentioning
confidence: 99%